Urgensi Hukum Non-Diskriminasi dalam Diversi Anak Berhadapan dengan Hukum: Kasus Narkotika - Rachel Patrecia (JUNCTO: Jurnal Ilmiah Hukum, 2026)
The study analyzes the diversion procedures in the Juvenile Criminal Justice System Law (UU SPPA) and the obstacles to its implementation for children in conflict with the law related to narcotics in the context of Indonesia's Golden Generation 2045. This research employs a normative legal method with statutory, conceptual, and case approaches. The findings indicate that although the UU SPPA mandates the principle of non-discrimination (Article 2) and diversion as a priority (Article 5 paragraph 3), there exists a legal gap between Article 7 paragraph 2 of the UU SPPA and the criminal sanctions in the Narcotics Law, which causes children to lose their right to diversion. Hidden discriminatory practices are evident in the differential treatment between child users (Article 127) who tend to receive diversion and child dealers (Article 114) who are criminalized, despite both being victims of exploitation. The main obstacles include: legal gaps in regulations, inconsistency in court decisions, differing perspectives among law enforcement officials, lack of cross-sectoral coordination, limited rehabilitation infrastructure, and social stigmatization. These conditions threaten the achievement of Indonesia's Golden Generation 2045. The study recommends harmonizing the UU SPPA with the Narcotics Law, establishing Joint Regulations among law enforcement agencies or creating Memoranda of Understanding (MoU), strengthening rehabilitation facilities, and conducting public education to reduce stigma.